Investigating The Nexus of Job Satisfaction, Transformational Leadership, and Employee Loyalty on Gen-Z Employees: Evidence from Jakarta - Titanicko, Titanicko; Pangaribuan, Christian Haposan (Sahabat Publikasi, 2025)
Employee loyalty is a critical factor in ensuring organizational sustainability, particularly in managing the emerging Gen-Z workforce. Previous studies have shown inconsistent findings regarding the influence of job satisfaction and transformational leadership on employee loyalty, indicating a theoretical and empirical research gap. This study aims to develop Social Exchange Theory (SET) by examining the role of job satisfaction and transformational leadership in fostering employee loyalty among Gen-Z employees in Jakarta. A quantitative approach was employed using purposive sampling as a non-probability sampling technique, resulting in 151 valid responses from a total population of 797,394 Gen-Z workers. Data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS) via SmartPLS 4.0 software. The results show that job satisfaction has a significant and positive effect on employee loyalty, confirming the relevance of reciprocal relationships emphasized in SET. However, transformational leadership was found to have no significant effect on employee loyalty, suggesting that leadership style alone may not directly influence Gen-Z’s commitment without the presence of other mediating factors. The study concludes that enhancing job satisfaction is a more effective strategy in building loyalty among Gen-Z employees than relying solely on leadership style. These findings have practical implications for human resource practitioners and organizational leaders in designing employee retention strategies tailored to younger generations. Future research is recommended to explore potential mediators or moderators in the relationship between leadership and loyalty.